1999
DOI: 10.1002/(sici)1096-9853(199911)23:13<1473::aid-nag34>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on problems associated with finite element excavation analysis by the stress-flow coupled method

Abstract: SUMMARYThis study attempts to address some problems associated with excavation analysis by means of the stress-#ow coupled method. This is done through the investigation of two examples, both of which are excavation analyses modelling a sequential excavation process. The "rst example is a three-dimensional elastic analysis of a tunnel constructed in soft rock layer. The second example is an axi-symmetric elasto-plastic analysis of a shaft constructed in slightly overconsolidated clay layer. In order to clarify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Several other cavity expansion theories have been developed in geomechanics, for field tests such as pressuremeter test and cone penetration test, [23][24][25][26][27][28][29][30][31][32][33] bearing capacity of piles, [34][35][36] and also tunnels and pipes. [37][38][39][40][41][42] Geomechanics has shown more interest in plasticity and failure conditions than in elastic conditions. 43 The cylindrical coordinates for plane strain are r, θ, and z.…”
Section: Solution For Full Penetration Of a Confined Aquifermentioning
confidence: 99%
“…Several other cavity expansion theories have been developed in geomechanics, for field tests such as pressuremeter test and cone penetration test, [23][24][25][26][27][28][29][30][31][32][33] bearing capacity of piles, [34][35][36] and also tunnels and pipes. [37][38][39][40][41][42] Geomechanics has shown more interest in plasticity and failure conditions than in elastic conditions. 43 The cylindrical coordinates for plane strain are r, θ, and z.…”
Section: Solution For Full Penetration Of a Confined Aquifermentioning
confidence: 99%
“…Numerical analysis of underwater tunnels, such as that presented by Ohtsu, Ohnishi, and Taki (1999), is a rather complex hydro-mechanical problem and cannot easily reveal the actual effects of water pressure on behaviour of the tunnel. Accordingly, analytical solutions of simpler cases preferred for preliminary design of underwater tunnels, e.g., circular tunnels excavated in elastic or elasto-plastic materials considering axisymmetric condition and uniform far-field stresses, facilitate estimation of stresses and deformations in the surrounding ground.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that soil plasticity affected the prediction of ground movement up to one radius beyond the tunnel cavity. 6) Ohtsu et al (1999) compared 3D finite element (FE) analysis with coupling of deformation and water flow to 2D analysis with plane strain condition. They concluded that for elasto-plastic analyses, the stress path in 2D FE analysis would have satisfied the yield condition, whereas that in 3D analysis remained in the elastic regime owing to drainage from the tunnel face.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the more permeable the ground was, the farther away the stress path was from the failure envelope. 7) Akagi and Komiya (1996), Komiya, et al (1999) proposed the concept of "excavation elements" to represent distorted material in front of the shield tunnel boring machine (TBM) in conjunction with a remeshing procedure for modeling the excavation of the tunnel face. 8), 9) Sugimoto and Sramoon (2002) proposed a kinematic shield model to simulate shield TBM behavior during excavation on the basis of equilibrium conditions by considering ground displacement around the shield, 10) and extended their investigation to shield tunneling behavior along a curved alignment in a multilayered ground.…”
Section: Introductionmentioning
confidence: 99%